The emergence of protowords: empirical evidence on the gradual convergence of parameters of wordiness - Karousou, Alexandra; Katis, Demetra; Stambouliadou, Chrysoula (Psychology: the Journal of the Hellenic Psychological Society, 2008)
Research on the emergence of “protowords” at the end of infancy stumbles upon methodological and theoretical problems. Since the early traces of words are sparse, unstable and, partly at least, of indeterminable meaning and idiosyncratic form, it is difficult to even record them, much more describe them with theoretical tools that are appropriate for adult words. If indeed development is a long-term, gradual and multidimensional process, as some theoretical approaches claim, a question is raised as to which properties constitute an utterance linguistic, how they converge and more generally how greater degrees of wordiness develop. The present study contributes to the discussion through a microgenetic analysis of two children’s utterances who were videotaped weekly between 8 and 24 months. Α total of 14.357 utterances were coded in terms of three parameters: phonoprosodic shape, relevance to the situation of use and conventionality. Their developmental pattern turned out to be similar for both children, in spite of some interesting divergences. Utterances with or without the above properties of wordiness coexist, although the former dramatically increase with time. Phonoprosodic shape has already emerged at 8 months and relevance of use at 9 months, followed very soon by the convergence of these two parameters. Shortly after, conventionality appears, even though it lags behind in the end. We argue that the data support theories which claim a gradual and multidimensional transition from prelinguistic to linguistic utterances.